Boden und Bodennutzung im Gulmaland (Südost Burkina Faso) - Semmel, Arno (ERDKUNDE, 1992)
Settlement density in the planation surfaces region of eastern Burkina Faso varies greatly. As a rule this does not depend on the occurrence of varying soil conditions, but on the settlement regions of different ethnic groups, on water supplies, and the availability of natural shelter. Traditional hoe cultivation as practiced by the Gulmance nonetheless shows very specific consideration for particular soil qualities. In this water-balance and cultivability of the soils are more important than nutrient supplies. This applies to the soil associations of laterite erosion surfaces in the crystalline areas, as well as to the sandstone complex of the Chaine de Gobnangou ridge. Hoe cultivation in small field units has hitherto not caused any catastrophic damage through soil erosion. *) Dieser Aufsatz ist dem Gedenken an Herrn Professor Dr. EIKE HABERLAND gewidmet, dem am 6. 6.1992 verstorbenen Initiator und Sprecher des SFB 268 Kulturentwicklung und Sprachgeschichte im Naturraum westafrikanische Savanne .